Synthesis, Characterization and Antimicrobial Activities of Some Nicotinamide – metal Complexes - A Lawal; J A Obaleye; J F Adediji; S A Amolegbe; M O Bamigboye; M T Yunus- Issa (Journal of Applied Sciences and Environmental Management, 2014)
Some transition metal complexes of nicotinamide have been prepared and characterized using melting point, conductivity measurement, infrared, electronic, HNMR and atomic absorption spectroscopic methods. . The antibacterial and antifungal studies of the metal complexes and the ligand have been evaluated against Escherichia coli, Staphylococcus and Bacillus subtilis , Aspergillus flavus, Aspergillus niger and penicillum species. It was found that nicotinamide formed stable metal complexes with these metal ions. The analysis of the spectroscopic data shows that nicotinamide act as monodentate, coordinating through the nitrogen atom of the pyridine ring. All the complexes exhibit 4- coordinate geometry. The results of the antimicrobial studies showed that the metal complexes have higher inhibitory activity than the original nicotinamide against the tested bacteria and fungi species.